2018
DOI: 10.1186/s40246-018-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of exonic rearrangements and frame shifts in the dystrophin gene in Duchenne muscular dystrophy patients in a Saudi community

Abstract: BackgroundIn individuals with Duchenne muscular dystrophy (DMD), exon skipping treatment to restore a wild-type phenotype or correct the frame shift of the mRNA transcript of the dystrophin (DMD) gene are mutation-specific. To explore the molecular characterization of DMD rearrangements and predict the reading frame, we simultaneously screened all 79 DMD gene exons of 45 unrelated male DMD patients using a multiplex ligation-dependent probe amplification (MLPA) assay for deletion/duplication patterns. Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
1
17
1
Order By: Relevance
“…Furthermore, admixture among different geographical populations might increase genetic variations and perhaps create new genotypic combinations within non-isolated (or non-native) populations. 45 Thus, genetic variations among some Middle Eastern individuals (e.g., Barbarians in North Africa, Kurdish, Upper Egyptian) [46][47][48][49] should be handled with caution, as increased consanguinity, reproductive isolation, and admixture with native source populations (e.g., Black Africans, South Eastern Asians, Caucasians) have considerable roles in gene flow and founder effects in these populations. For instance, the frequency of the 677T allele is often reported to be high in Europeans and North Americans, to be low in East Asians and Africans, and to show geographical gradients in areas of Europe, North America, and India.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, admixture among different geographical populations might increase genetic variations and perhaps create new genotypic combinations within non-isolated (or non-native) populations. 45 Thus, genetic variations among some Middle Eastern individuals (e.g., Barbarians in North Africa, Kurdish, Upper Egyptian) [46][47][48][49] should be handled with caution, as increased consanguinity, reproductive isolation, and admixture with native source populations (e.g., Black Africans, South Eastern Asians, Caucasians) have considerable roles in gene flow and founder effects in these populations. For instance, the frequency of the 677T allele is often reported to be high in Europeans and North Americans, to be low in East Asians and Africans, and to show geographical gradients in areas of Europe, North America, and India.…”
Section: Discussionmentioning
confidence: 99%
“…Recently in 2018, A study done in Saudi Arabia by Elhawary et al, [19] the authors used multiplex PCR and MLPA to identify gene mutation, they found 46.3% deletions and 53.7% duplications in the DMD gene, they also identified seven previously undescribed large DMD rearrangements. These new mutations included mixed rearrangement, large deletion, large duplications and double duplications.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in mean full scale intelligence quotient (FSIQ), by approximately one standard deviation, with respect to the population mean, has remained a consistent finding in the cognitive profile in these patients 5 . DMD is manifested by rearrangement events including deletion, duplication and point mutations in DMD gene which create a shift in the reading frame that result in non-functional dystrophin protein 6,7 . DMD gene locus produces full length and short sized dystrophin products from seven distinct promoters.…”
mentioning
confidence: 99%